2017
DOI: 10.1016/j.ijimpeng.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibre orientation on the low velocity impact response of thin Dyneema® composite laminates

Abstract: Ultra-high molecular weight polyethylene (UHMWPE) fibre reinforced composite materials are widely used in ballistic impact and collision scenarios due to their extremely high specific strength and stiffness. Exceptional levels of protection are provided by controlling the damage and deformation mechanisms over several length scales. In this study, the role of UHMWPE fibre architecture (cross-ply, quasi-isotropic and rotational "helicoidal" layups) is considered on the damage and deformation mechanisms arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 13 publications
3
37
0
Order By: Relevance
“…In particular the displacement obtained by the drop tower was indirectly measured from Equation 4. As in [15], the DIC accuracy was also affected by the indirect capture of the target plate out of plane displacement due to the use of a mirror, which reflected and projected the superficial speckle pattern. The effect of the impact energy level was also considered in this preliminary study.…”
Section: Steel Impactor On a Deformable Platesmentioning
confidence: 94%
See 2 more Smart Citations
“…In particular the displacement obtained by the drop tower was indirectly measured from Equation 4. As in [15], the DIC accuracy was also affected by the indirect capture of the target plate out of plane displacement due to the use of a mirror, which reflected and projected the superficial speckle pattern. The effect of the impact energy level was also considered in this preliminary study.…”
Section: Steel Impactor On a Deformable Platesmentioning
confidence: 94%
“…A schematic representation of the experimental set-up, similar to the one proposed by Hazzard et al in [15], is shown in Figure 1. The geometry of the low test area, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly commercialised polyethylenereinforced composite panels (such as Dyneema ® HB25, HB26) consist of hotpressed layers of unidirectionally aligned fibers at 0°/90°. Even though this configuration enhances a good level of resistance to penetration, alternative orientations of the helmet layers leading to a quasi-isotropic behaviour provide a considerable decrease of BFD [239,241,243].…”
Section: Effect Of Stack Configuration Of the Helmet Shellmentioning
confidence: 99%
“…A possible reinforcement of this configuration (#P2) would be to consider each composite layer as a Dyneema HB26 stack. The latter, schematically represented in Fig.7.1 (right), is conformed by alternating plies of UHMWPE fibres oriented at 0°and 90°which are stacked by means of hot-pressing [243,250]. This cross-ply structure enables the assumption of a layer-level orthotropic behaviour [250].…”
Section: Shell Configurationsmentioning
confidence: 99%